2015
DOI: 10.1088/1367-2630/17/1/013004
|View full text |Cite
|
Sign up to set email alerts
|

The role of heavy metal ions on spin transport in organic semiconductors

Abstract: It is generally believed that spin-orbit coupling (SOC) strength and the associated spin relaxation can be enhanced by introducing heavy metal ions in organic semiconductors. Here, we systematically study the spin transport in two organic semiconductors, tris(2-phenylpyridine)iridium (Ir(ppy) 3 ) and tris-(8-hydroxyquinoline) aluminum (Alq 3 ), which have similar chemical structures except that Ir(ppy) 3 contains a heavy metal ion Ir. As expected, the photoluminescence spectroscopy measurements show that the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Figure f shows the temperature dependence of GMR measured by Xiong et al They observed a large GMR effect at low temperatures but the effect reduced considerably with increasing the temperature and vanished at room temperature. Similar dependence of the GMR on temperature has been reported with other organic molecules and polymers as well . Either the reduction of the electrode spin polarization or of the spin diffusion length at high temperature can be responsible for the reduction of the GMR at increased temperatures.…”
Section: Fundamental Conceptssupporting
confidence: 80%
See 3 more Smart Citations
“…Figure f shows the temperature dependence of GMR measured by Xiong et al They observed a large GMR effect at low temperatures but the effect reduced considerably with increasing the temperature and vanished at room temperature. Similar dependence of the GMR on temperature has been reported with other organic molecules and polymers as well . Either the reduction of the electrode spin polarization or of the spin diffusion length at high temperature can be responsible for the reduction of the GMR at increased temperatures.…”
Section: Fundamental Conceptssupporting
confidence: 80%
“…Therefore, this spin diffusion length measurement technique has unavoidable uncertainty. Figure shows the MR values (normalized to their maximum) measured as a function of the interlayer thickness and their modified‐Jullière fit for representative OSCs as extracted from different studies . The figure depicts a general trend that the MR decreases significantly with the thickness and vanishes at a certain thickness.…”
Section: Advances In Organic Spin Valvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Index Terms-Organic, spin-pumping, Spintronics, transport I. INTRODUCTION pin transport experiments of various organic molecular materials have been conducted in recent years [1][2][3][4][5][6]. Previously, our group achieved spin transport in thermally evaporated pentacene films [1].…”
mentioning
confidence: 99%